2009
DOI: 10.1063/1.3075814
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, electronic, and phonon properties of zinc-blende and wurtzite BeO

Abstract: The results of ab initio calculations of the structural, elastic, electronic, and phonon properties of BeO in both zinc-blende and wurtzite structures are presented. Our calculations are based on the application of plane-wave basis, pseudopotentials, and the generalized gradient approximation of the density functional scheme. Our total energy calculations indicate that the wurtzite phase has lower energy (around 5.8 meV) than zinc-blende phase. It is found that for the two crystal phases the values of the equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 34 publications
7
23
0
Order By: Relevance
“…BeO compound often has different properties from the counterpart of C and BN nanotube (BNNT) because of the large ionicity of Be-O bond. For example, wurtzite BeO is an insulator with a wide band gap, high melting point, high thermal conductivity and large elastic constants [15]. In addition, compared with CNTs and BNNTs, it was found that the BeONTs have larger band gap which is less dependent on the chirality and diameter of tubes [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…BeO compound often has different properties from the counterpart of C and BN nanotube (BNNT) because of the large ionicity of Be-O bond. For example, wurtzite BeO is an insulator with a wide band gap, high melting point, high thermal conductivity and large elastic constants [15]. In addition, compared with CNTs and BNNTs, it was found that the BeONTs have larger band gap which is less dependent on the chirality and diameter of tubes [16,17].…”
Section: Introductionmentioning
confidence: 98%
“…Its phase transformation behaviours under pressure have been studied by theoretical calculations 6–8 and experiments 9. Ab initio calculations have been performed to calculate structural property, electronic structure and optical property of wurtzite BeO and metastable high pressure polymorphs of BeO with zinc‐blende and rocksalt structures 4, 5, 10–14.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the carbon nanotube, other nanotube such as BN, BC 2 N, and SiC also have attracted much attention. 15 The conduction band bottom of BeO sheet is the nearly freeelectron state, while that of C, BN, and SiC is the ‫ء‬ state. [12][13][14] BeO compound often has different properties from the counterpart of C, BN, and SiC, due to the large iconicity of Be-O bond.…”
Section: Modulating the Electronic Structures And Optical Absorption mentioning
confidence: 99%